Tsetse fly-transmitted African trypanosomiasis - Lehane, Mike (Henry Stewart Talks, 2010)
Sleeping sickness and nagana, Major treatments, Shortcomings of current treatment regimes and why vector control is important, Introduction to tsetse biology, Primary methods of tsetse fly control